2009
DOI: 10.20886/jpht.2009.6.1.1-8
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH UKURAN BENIH TERHADAP PERKECAMBAHAN DAN PERTUMBUHAN BIBIT MINDI (Melia azedarach L.)

Abstract: Key words : Germination, mindi (M. azedarach), seedling growth, seed size/weight ABSTRAK Pengadaan benih untuk meningkatkan keberhasilan penanaman memerlukan benih dalam jumlah dan mutu yang baik. Permasalahan yang terkadang muncul dalam rangka pengadaan benih adalah menentukan cara seleksi benih yang memiliki mutu fisiologis yang tinggi, salah satunya berhubungan dengan ukuran benih. Benih mindi (Melia azedarach) mempunyai ukuran bervariasi. Penelitian seleksi benih mindi dilakukan karena adanya dugaan bahwa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
0
4
1
10
Order By: Relevance
“…Contrary to the results of this study, Mimusops elengi (Suita and Nurhasybi 2008) and Dalbergia sissoo (Singh et al 2011) were reported to have different result, namely that their seeds size did not show a different effect on their germination capacity. Likewise, the seeds of soybean showed that the large seeds possessed a lower seed amount and germination capacity than those of medium and smaller seeds (Yulyatin and Diratmaja.…”
Section: The Influence Of Seed Size On Filled Seeds Germination Andcontrasting
confidence: 98%
See 2 more Smart Citations
“…Contrary to the results of this study, Mimusops elengi (Suita and Nurhasybi 2008) and Dalbergia sissoo (Singh et al 2011) were reported to have different result, namely that their seeds size did not show a different effect on their germination capacity. Likewise, the seeds of soybean showed that the large seeds possessed a lower seed amount and germination capacity than those of medium and smaller seeds (Yulyatin and Diratmaja.…”
Section: The Influence Of Seed Size On Filled Seeds Germination Andcontrasting
confidence: 98%
“…Several research reports found that seed size affected the rate of germination and growth of some crops and forest tree species. Bigger-sized seeds of Mimoseps elengi possessed a greater rate of germination and growth compared to smaller-sized seeds (Suita and Nurhasybi 2008). As well as, small seeds of Thlaspi arvense (Susko and Cavers 2008) and Macadamia sp.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Benih yang berukuran besar mempunyai kecenderungan untuk berkecambah dan tumbuh lebih baik. Misalnya pada benih mindi, tanjung, dan kemenyan (Winarni dan Suita, 2009;Suita, 2011;Sorensen dan Campbell, 1993;Suita dan Megawati, 2009;Suita dan Nurhasybi, 2008;Suita dan Megawati, 2008) Adanya variasi berat dan ukuran benih dari masing-masing lokasi dipengaruhi oleh faktor keturunan (genetik) dari pohon induk dan lingkungan. Benih yang berasal dari pohon induk yang berbeda mungkin akan mempunyai keragaman berat dan ukuran yang berbeda dan mempunyai respon yang berbeda pula terhadap daya berkecambah dan vigor benihnya sehingga antara lot-lot benih dalam satu jenis yang berbeda pohon induk atau provenannya ada kemungkinan berkorelasi dan tidak berkorelasi dengan daya berkecambah dan vigor benih (Sudrajat, 2006).…”
Section: B Pembahasanunclassified
“…Penelitian sebelumnya menggambarkan untuk jenis-jenis tertentu benih besar memiliki kualitas yang lebih baik daripada benih kecil. Suita (2009) …”
unclassified